Impact of hemorrhoidectomy with lateral internal sphincterotomy on resting anal pressure in grade III and IV haemorrhoids with elevated anal pressure (>90 mmHg): a prospective observational study - Jeevarathinam, Rudhirappa; Kandhasamy, Sakthivel Chinnakkulam; Jithu, Thulaseedharan Girija; Zachariah, Sanoop Koshy (International Journal of Research in Medical Sciences, 2026)
Background: Grade III and IV hemorrhoids commonly present with pain, bleeding and prolapse, often associated with elevated resting anal pressure. This study assessed postoperative changes in anal pressure and their relationship with disease grade, surgical procedure and outcomes. Methods: This 18-month prospective study included 79 patients with Grade III–IV hemorrhoids and elevated resting anal pressure, evaluating postoperative pressure changes and their association with symptoms, disease severity and hemorrhoidectomy type. Results: The mean age was 44.6±12.4 years; 67.1% were male, with most patients aged 31–40 years. Perianal pain was present in all patients, followed by bleeding (n=44) and prolapse (n=34). Grade III and IV hemorrhoids were seen in 43% (n=34) and 57% (n=45), respectively; 53.2% underwent open and 46.8% stapler hemorrhoidectomy. Preoperative VAS scores were similar between groups (p=0.898). Median VAS significantly decreased from 6 (IQR 5–7) preoperatively to 2 (IQR 1–2) on POD1 and 1 (IQR 0–1) on POD7 (p<0.001). On POD1, 84.8% had mild pain, 11.4% no pain and 3.8% moderate pain; by POD7, 36.7% were pain-free and 63.3% had mild pain. Complications included bleeding (n=17), urinary retention (n=12) and faecal incontinence (n=3). Mean resting anal pressure decreased from 122.9±7.50 mmHg preoperatively to 83.4±7.42 mmHg at 1 week and 90.9±7.63 mmHg at 2 months (p<0.001), with recurrence in only two stapler hemorrhoidectomy patients at 3 months. Conclusions: Grade III–IV hemorrhoid surgery significantly reduces symptoms and resting anal pressure, with both open and stapler hemorrhoidectomy showing similar efficacy, low complications and minimal recurrence.